2013
DOI: 10.1038/nchembio0313-192a
|View full text |Cite
|
Sign up to set email alerts
|

Addendum: Chemical inhibitor of nonapoptotic cell death with therapeutic potential for ischemic brain injury

Abstract: In this Article 1 , we described a small-molecule inhibitor of necroptosis, termed Necrostatin-1 (Nec-1). Since the original publication, additional data regarding the properties of Nec-1 have been reported, including off-target activity and metabolic stability in mice, that are important in designing in vitro and, especially, in vivo experiments with Nec-1.Teng et al. 2 reported an optimized derivative of Nec-1, termed 7-Cl-O-Nec-1 (66 in ref.2), that was used in ref. 1 to demonstrate the protection in an isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…We recently conducted the first untargeted lipidomic analysis of necroptotic cells and identified lipid participants of this process . Necroptosis is a form of regulated cell death that exhibits phenotypic hallmarks of necrotic cell death including cell and organelle swelling and the permeabilization of cellular membranes upon activation of the death pathway . The permeabilization of the plasma membrane, in particular, results in the release of cytokines and other molecules to the extracellular matrix, which can result in an inflammatory response at the organismal level. , In an effort to identify lipids involved in membrane permeabilization during necroptosis, we analyzed the changes in lipid composition in multiple cell lines during this process.…”
mentioning
confidence: 99%
“…We recently conducted the first untargeted lipidomic analysis of necroptotic cells and identified lipid participants of this process . Necroptosis is a form of regulated cell death that exhibits phenotypic hallmarks of necrotic cell death including cell and organelle swelling and the permeabilization of cellular membranes upon activation of the death pathway . The permeabilization of the plasma membrane, in particular, results in the release of cytokines and other molecules to the extracellular matrix, which can result in an inflammatory response at the organismal level. , In an effort to identify lipids involved in membrane permeabilization during necroptosis, we analyzed the changes in lipid composition in multiple cell lines during this process.…”
mentioning
confidence: 99%
“…Programmed necrosis is cell death independent of caspase and is always triggered as a backup mechanism for apoptosis when caspases are inactivated. In addition, programmed necrosis is accompanied by autophagy, but the specific relationship remains an enigma [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was demonstrated that this cell death process is dependent on receptor-interacting serine/threonine kinase 1 (RIPK1) and can be inhibited by necrostatin 1 (Nec-1). 62,63 Subsequently, necroptosis was better defined as a RIPK3-dependent molecular cascade promoting regulated necrosis 218 based on the discovery of a close interaction between RIPK1 and its homolog RIPK3 in transducing pronecrotic signals, 47,134,344 and on the identification of multiple RIPK3-dependent but RIPK1-independent instances of regulated necrosis such as in murine cytomegalovirus infections, nitric oxide (NO)-induced pancreatic beta-cell death, and cell death in fibroblasts. 156,282,291,297 This understanding was further enhanced by the discovery of mixed lineage kinase domain-like pseudokinase (MLKL) as the effector of necroptosis (Figs.…”
Section: Necroptosismentioning
confidence: 99%